90.5k views
24 votes
Pls helpppp asapppp with the question above

Pls helpppp asapppp with the question above-example-1
User Reki
by
5.9k points

2 Answers

14 votes

Answer:

0

Explanation:

4(m+2) = -4(m-2)

by dividing over 4 :

m+2 = -1(m-2)

= m+2 = -m+2

by subtracting 2 :

m = -m

by adding "m" :

2m = 0

So

m = 0

I hope that the explanation is clear for you.

User Kedor
by
6.3k points
8 votes

Answer:

the answer should be B

Explanation:

i do apologize if its wrong im like 99.9% sure it correct

User Jasssonpet
by
6.1k points